التوافق الاسري وعلاقته بجودة الحياة لدى الاسر بولاية الوادي - برتيمة,رانيا; مختاري,نجود (University of Eloued جامعة الوادي, 2024)
ملخص الدراسة بالعربية: استهدف هذه الدراسة العلاقة بين التوافق الأسري وجودة الحياة لدى الأسر بولاية الوادي، ومعرفة إن كانت هناك فروق بين أفراد العينة في المتغيرين (التوافق الأسري وجودة الحياة) والتي يمكن أن تعزى إلى الجنس (ذكر / أنثى) . شملت عينة البحث (49 أسرة من أسر ولاية الوادي) تمادت (20 منهم ذكور و29 إناث). واستخدم في الدراسة مقياسان لغرض جمع البيانات اللازمة وهما: مقياس التوافق الأسري لمحمد عبد الحميد 1986، ومقياس جودة الحياة رنا فاضل عباس الجنابي 2023. تمت معالجة البيانات إحصائيا باستخدام البرنامج الإحصائي (Spss) الذي سمح بتطبيق الأدوات الإحصائية التالية: ارتباط (T_TEST) لعينة واحدة، معامل الارتباط برسون، وتوصلت الدراسة الى جملة من النتائج ابرزها: _ يتمتع الأسر بمستوى متوسط من جودة الحياة. _ وجود علاقة ارتباطية ذات دلالة إحصائية بين التوافق الأسري وجودة الحياة لدى الأسر بولاية الوادي. _ لا توجد فروق ذات دلالة إحصائية في جودة الحياة تبعا لمتغير الجنس (ذكور _ إناث) . Abstract: This research aimed to study the relationship between family harmony and quality of life among families in the state of El Oued, and to find out if there are differences between the sample members in the two variables (family harmony and quality of life) that can be attributed to gender (male/female) . The research sample included (49 families from the state of El Oued) (20 of them males and 29 females) . Two scales were used in the study to collect the necessary data: the family harmony scale and the quality of life scale . The data were processed statistically using the statistical program (spss), which allowed the application of the following statistical tools: correlation (T_TEST) for one sample, Pearson correlation coefficient ,The results were as follows : Families enjoy an average level of quality of life. This research aimed to study the relationship between family harmony and quality of life among families in the state of El Oued, and to find out if there are differences between the sample members in the two variables (family harmony and quality of life) that can be attributed to gender (male/female). .
Keywords: التوافق الاسري; جودة الحياة; Family compatibility; Quality of life